Understanding Degradation Effects of Elevated Temperature Operating Conditions in Polymer Electrolyte Water Electrolyzers. Issue 4 (14th April 2021) - Garbe, Steffen; Futter, Jonas; Agarwal, Ayush; Tarik, Mohamed; Mularczyk, Adrian A.; Schmidt, Thomas J.; Gubler, Lorenz
Abstract : The cost of polymer electrolyte water electrolysis (PEWE) is dominated by the price of electricity used to power the water splitting reaction. We present a liquid water fed polymer electrolyte water electrolyzer cell operated at a cell temperature of 100 °C in comparison to a cell operated at state-of-the-art operation temperature of 60 °C over a 300 h constant current period. The hydrogen conversion efficiency increases by up to 5% at elevated temperature and makes green hydrogen cheaper. However, temperature is a stress factor that accelerates degradation causes in the cell. The PEWE cell operated at a cell temperature of 100 °C shows a 5 times increased cell voltage loss rate compared to the PEWE cell at 60 °C. The initial performance gain was found to be consumed after a projected operation time of 3, 500 h. Elevated temperature operation is only viable if a voltage loss rate of less than 5.8 μ V h −1 can be attained. The major degradation phenomena that impact performance loss at 100 °C are ohmic (49%) and anode kinetic losses (45%). Damage to components was identified by post-test electron-microscopic analysis of the catalyst coated membrane and measurement of cation content in the drag water. The chemical decomposition of the ionomer increases by a factor of 10 at 100 °C vs 60 °C. Failure by short circuit formation was estimated to be a failure mode after a projected lifetime 3, 700 h. At elevated temperature and differential pressure operation hydrogen gas cross-over is limiting since a content of 4% hydrogen in oxygen represents the lower explosion limit.